Análisis jurídico de la judicialización del acceso a los medicamentos y el Derecho Constitucional a la Salud en los Hospitales de alta complejidad del IESS. - Larrea Quijano, Patricio Benjamín (2024)
The primary objective of this research project is to carry out a legal analysis of the right to health of Ecuadorian citizens. How is this right legally established in national regulations? What is its scope? What are its limitations? And, what happens when it legally constitutes a duty of the State to ensure that this right is effective and timely? The Ecuadorian Social Security Institute of Ecuador, through its health centers, serves all citizens who have joined this institution; which is mandatory. It must be emphasized that today, an employer who does not affiliate workers under his supervision in Ecuadorian legislation, even constitutes a crime. So much so that the Ecuadorian Social Security Institute has the obligation to protect and care for, within its powers, essentially the health of its users. However, problems constantly arise due to the lack of medications to treat catastrophic diseases and even those that are clinically called orphans; stripping the person who suffers from them of their right to health. The aforementioned has reached the point that users of the IESS have to file complaints before the jurisdictional bodies of the judicial function and even before the Constitutional Court to proceed with the acquisition of medicines to address this very complex problem, which unfortunately is constant in the Ecuadorian State and from there the judicialization of medicines is derived. To carry out this research, I resorted to reviewing existing sentences of cases that have been presented and that have constituted a starting point, so that the right to health is legally protected. The conduct of this investigative study is justified in relation to the right to health enshrined in our supreme norm and its violation due to the lack of provision of necessary medications in the IESS hospitals. This is an institute that is maintained through the 6 contributions of its members and therefore has its own resources and it is unjustifiable that the hospitals of the Ecuadorian Institute of Social Security do not have the necessary medications to treat high-risk, catastrophic and high-priority diseases. During the development of this work, several methodologies will be used. Descriptive methodology: this type of methodology is used to describe the characteristics of a phenomenon that is being studied, in this case the judicialization of medications. Explanatory methodology: by using this methodology the aim is to identify and determine the causes of the problem that is the object of this study. This work attempts to obtain a constitutional analysis of the right to health and its scope, in addition to presenting an analysis of sentences in which the object of controversy has been the judicialization of access to medicines. It also seeks to investigate and determine the legal effects generated in our regulatory framework by the sentences issued in relation to the topic discussed in this investigation. Keywords: Judicialize, right to health, medications, orphan diseases, highly complex hospitals.